2021
DOI: 10.3892/etm.2021.9892
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic acid restrains airway inflammation and remodeling in asthma via the TGF‑β1/Smad signaling pathway

Abstract: The anti-inflammatory effects of glycyrrhizic acid (GA) against asthma have previously been reported; however, the underlying molecular mechanism of GA in asthma has not yet been elucidated. Thus, the present study aimed to determine the function and potential molecular mechanism of GA for modulating the transforming growth factor-β1 (TGF-β1)/Smad signaling pathway in asthma-associated airway inflammation and remodeling. In order to study the mechanism of GA on airway inflammation and airway remodeling in asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Tu et al reported that in the liver and spleen of murine fibrosis models, glycyrrhizin upregulated both Th1/Th2 and Treg/Th17 balances to Th1- and Treg-dominant lineages via multiple pathways such as via c-Jun amino terminal kinase, extracellular signal-regulated kinase and PI3K/AKT [ 32 ]. In another study, it was shown that GA reduced airway inflammation and remodeling via the TGF-β1/Smad signaling pathway [ 33 ]. The exact mechanism of the immune response modulating in AIT by GA is still unknown and requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…Tu et al reported that in the liver and spleen of murine fibrosis models, glycyrrhizin upregulated both Th1/Th2 and Treg/Th17 balances to Th1- and Treg-dominant lineages via multiple pathways such as via c-Jun amino terminal kinase, extracellular signal-regulated kinase and PI3K/AKT [ 32 ]. In another study, it was shown that GA reduced airway inflammation and remodeling via the TGF-β1/Smad signaling pathway [ 33 ]. The exact mechanism of the immune response modulating in AIT by GA is still unknown and requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…47 Transforming growth factor-1 (TGF-β1) is the main regulator that can promote airway fibrosis and collagen deposition by regulating cytokines such as Smads proteins. 48 In the treatment of diabetic nephropathy, many benefits such as antiallergic and anti-inflammatory effects and enhancement of body fluid and cellular immunity. 62 This evidence vouches for the high safety of the clinical application of icariin and its feasibility in treating asthma, providing support for further clinical application of icariin.…”
Section: Icariin Could Inhibit Extracellular Matrix (Ecm) Depositionmentioning
confidence: 99%
“…ex DC., where its anti-inflammatory activity has also been proved in a past study (Yang et al, 2017). GA (Yao and Fu, 2021) can significantly alleviate airway inflammation, inflammatory cell infiltration, and remodeling in vitro and markedly restore the thickness of ASM and airway walls in vivo, which is at least partly associated with the modulation of the TGF-β1/Smad signaling pathway. It is worth noting that the study was the first to investigate that GA may suppress chronic asthma symptoms.…”
Section: The Saponinsmentioning
confidence: 80%